Critical View on The Existence of Gambus Tunggal Lampung: Promoting Collaborative Working Between Artists and Stakeholders - Tejapermana, Prisma; Hidayatullah, Riyan (Harmonia: Journal of Arts Research and Education, 2020)
The Lampung societies have many arts and cultures, one of which is a gambus tunggal. The characteristic of gambus that are played solely and has an original tuning system. A gambus tunggal style produces a melodic tone, accompanied by chanted poems that involve new romantic romance of Lampung, or parents’ advice to their children. This ethnography study aims to comprehend how the gambus tunggal artists maintain the existence in Lampung. The study applies a descriptive method with a qualitative idea. We have interrogated and field studies to gather primary data. A purposive sampling technique was used to interview a gambus tunggal player who existed for decades. The result indicates that a gambus tunggal artist is doing a collaborative struggle to support gambus tunggal and living sources’ survival. They need collaboration to keep the existence of traditional Lampung music. Gambus players have considered using social media as a promotional strategy. The local government’s role has a tremendous impact, for example, providing an opportunity to perform gambus tunggal at various events, festivals, and many competitions. Therefore, the tourism sector is the foundation of Lampung’s traditional music. It establishes policies to serve various performing arts.